2016
DOI: 10.3319/tao.2015.11.05.01(t)
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Slip Distribution Self-Similarity on a Fault Surface

Abstract: The earthquake slip distribution self-similarity is investigated in this study. We complied finite fault slip models for earthquakes in the Taiwan orogenic belt and global earthquakes to determine the slip distribution self-similarity. Forty-one earthquakes (19 Taiwan earthquakes and 22 global earthquakes) in the M w = 4.6 -8.9 magnitude range were examined. The fault slip exhibited self-similar scaling between the rupture slip and area. The average area ratio (R s ) and slip ratio (R d ) follows a scaling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Finally, we scaled the slipped area partitioned within the finite fault proposed by Lee et al (2016) for slip-distribution heterogeneity. For large earthquakes with M w > 7.0, .…”
Section: Wavenumber Spectrum Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, we scaled the slipped area partitioned within the finite fault proposed by Lee et al (2016) for slip-distribution heterogeneity. For large earthquakes with M w > 7.0, .…”
Section: Wavenumber Spectrum Analysismentioning
confidence: 99%
“…In addition, they suggested that the slip distribution on a finite fault is the major concern in the forward simulation of earthquake scenarios. To define finite-fault heterogeneity Somerville et al (1999), Murotani et al (2008), and Lee et al (2016) examined earthquakes in California, Japan, and Taiwan, respectively. They reported that in approximately 20% of the total fault rupture area, the slips are 1.5 times larger than the average slip.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mandelbrot (1983) proposed the fractal geometry with fractal dimension to describe the scale-invariant natural phenomena. This concept has been applied to seismology (Turcotte 1989;Korvin 1992), including the fault properties (Aviles et al 1987;Okubo and Aki 1987;Lee and Schwarcz 1995;Candela et al 2012), the spatial distribution of earthquakes (Hirabayashi et al 1992;Turcotte 1997;Wang and Shen 1999), the temporal variation in earthquakes (Smalley et al 1987;Hirata 1989;Kagan and Jackson 1991;Ogata and Abe 1991;Papadopoulos and Dedousis 1992;Koyama et al 1995;Lee 1995, 1997;Wang 1996a;Kagan 2007;Michas et al 2014), and earthquake ruptures (Wang 1995(Wang , 1996bAochi and Ide 2004;Aochi 2005, 2014;Manighetti et al 2005;Lee et al 2016).…”
Section: Introductionmentioning
confidence: 99%